2010
DOI: 10.1038/cdd.2010.18
|View full text |Cite
|
Sign up to set email alerts
|

Combination of nutlin-3 and VX-680 selectively targets p53 mutant cells with reversible effects on cells expressing wild-type p53

Abstract: Chemotherapeutics (e.g., aurora kinase inhibitors) designed to target proliferative cells are often nonspecific for tumor cells as normal cycling cells are also susceptible. Indeed, one of the major dose-limiting toxicities of aurora kinase inhibitors is a dangerous depletion of neutrophils in patients. In this study we proposed a strategy to selectively target p53 mutant cells while sparing normal ones. The strategy is based on the understanding that normal cells have an intact p53 pathway but not tumor cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 38 publications
(50 reference statements)
3
41
0
Order By: Relevance
“…It may be that, in vivo increased CtBP abundance in certain tumours (Phelps et al, 2009) or potentially increased CtBP chromatin-modifying complex formation in hyper-glycolytic tumour cells (Zhang et al, 2002) may result in selective dependency upon CtBPs for mitotic fidelity in tumours compared with normal tissues; however, experiments in which specific CtBP functions are inactivated in adult cells in vivo would be required to address these questions. Importantly, however, in the case of aurora inhibitors, which do show some toxicity due to effects on neutrophils, cellular toxicity can be overcome by arrest of normal cells with low doses of a p53-activating agent (Cheok et al, 2010). We have previously shown that, in breast cancer cells, activation of wild-type p53 protects CtBP-siRNA-treated cells from dying, whereas cells with mutant p53 or p53 suppressed by siRNA, exhibit substantial apoptotic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that, in vivo increased CtBP abundance in certain tumours (Phelps et al, 2009) or potentially increased CtBP chromatin-modifying complex formation in hyper-glycolytic tumour cells (Zhang et al, 2002) may result in selective dependency upon CtBPs for mitotic fidelity in tumours compared with normal tissues; however, experiments in which specific CtBP functions are inactivated in adult cells in vivo would be required to address these questions. Importantly, however, in the case of aurora inhibitors, which do show some toxicity due to effects on neutrophils, cellular toxicity can be overcome by arrest of normal cells with low doses of a p53-activating agent (Cheok et al, 2010). We have previously shown that, in breast cancer cells, activation of wild-type p53 protects CtBP-siRNA-treated cells from dying, whereas cells with mutant p53 or p53 suppressed by siRNA, exhibit substantial apoptotic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…5 Exposure to nutlin-3, tenovin-6 (tnv6) or low doses of actinomycin-D (LDactD), for instance, increases p53 levels and activity leading to tumor cell death and/or inhibition of cell cycle progression. [6][7][8][9] These p53-dependent effects on cell viability and proliferation are most evident with nutlin-3. Another feature shared by these compounds is that they do not induce the appearance of DNA damage markers, suggesting that they activate p53 without causing extensive genotoxicity.…”
Section: Introductionmentioning
confidence: 91%
“…Such compounds should selectively induce p53-dependent G 1 and/or G 2 cell cycle arrest in normal tissues while leaving cancer cells lacking functional p53 vulnerable to subsequent treatment with S-or M-phase poisons. 30,31 Initial studies with nutlin-3 7,32,50,51 or LDactD 9,52 have yielded interesting and, in some cases, promising results.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, combinations of VX680 with other drugs, such as paclitaxel, cis-platinum, TSA and nutlin-3, have been proven to produce synergistic effects in malignant tumors. 25,[52][53][54] In the present study, we sought to identify a potential therapeutic partner for VX680 with a targeted and complimentary anti-cancer mechanism. We found that p-p38 and p-ERK were up-regulated after VX680 treatment, whereas the expression of Bcl-2 was not affected.…”
Section: Discussionmentioning
confidence: 99%